CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques